Reposition of GRDP Sectors Before and After Regional Division in Manokwari - Rahayu, Yuyun Puji; Semet, Maria Magdalena; Paembang, Suryna (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
Regional expansion could be a strength to improve the performance of local governments and subsequently should have a positive impact, such as improving the welfare of the local community. Regional expansion also aims to make governments at regional level to be more focused on escalating potential sectors in their regions. This study analyzes the repositioning of the GRDP contributing sector before and after expansion between two regency regions in 2010-2017, one parental Regency and one area that is separated from its parental. Repositioned sectors show the influence of an area in terms of its wealth of the resources as basis sector. The research method uses Location Quotient (LQ) and Shift Share analysis. Results of this study show that before and after expansion of districts into new regency, agricultural sector has declined in the contribution of GRDP. But after the expansion, the sectors with the best economic performance are the construction, administration and trade & repair sectors. In addition, agricultural sector to some extent has been decreased in the two regions. But at the same time, agricultural sector become leading sector in the new region with slow growth. Implication of this study is that the division of regions would not create new leading sector if the potential sector in a new region is the leading sector in the older region. Therefore, policy making which ensure basic sectors to have positive proportional shift and differential shift could drive economic development planning in both regions.Ã‚Â